Community Partnership Empowerment Waste Utilization Pig Manure in P4S Sedana Sari Strait Village, Biansemal-Badung - Yuliartini, Made Sri; Wirajaya, Anak Agung Ngurah Mayun; Sukmadewi, Desak Ketus Tristiana; Setiawan, Tasya Amelia; Todo, Modesta Sriayuningsi (Asian Journal of Community Services, 2024)
Community partnership empowerment was carried out at P4S Sedana Sari with the title "PKM Utilization of Pig Manure Waste at P4S Sedana Sari Selat Village, Abiansemal Badung.  The application of organic fertilizer technology in the agricultural sector is one of the efforts in sustainable agriculture.  Organic fertilizer technology in this case is manure produced from pig manure. There is quite a lot of manure waste which, if not processed, can cause environmental pollution such as air and water, so further handling of the livestock manure is necessary.  Making organic fertilizer is an alternative to using pig manure which can be processed as fertilizer for plants.  The method is technology transfer and introducing science and technology, namely outreach, training, mentoring activities, both partners are actively and creatively invited to work together. The resulting product is organic fertilizer with analysis and can be applied to plants.